GAMBARAN STATUS GIZI SISWA SDN 61 KOTA TIMUR KOTA GORONTALO - Febri Levina; M. Anas Anasiru; Salman Salman; Mutia Reski Amalia (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2021)
ABSTRACT School children are one of the nutritionally vulnerable groups who need attention to their nutritional status so that in the future they become quality human resources. This study aims to describe the nutritional status of students at SDN 61 Kota Timur Gorontalo City. The research method used is descriptive research. The population is students in grades II, III, IV, and V at SDN 61 Kota Timur Gorontalo City totaling 260 people. The sample of this study amounted to 158 people. The variables in this study are independent variables, namely the description of nutritional status. The results showed that from 158 respondents who were categorized as undernourished, 2 people (1.2%), good nutrition (normal) amounted to 88 people (55.8%), at risk of overnutrition amounted to 38 people (24%), over nutrition totaled 22 people (13.9%) and obesity amounted to 8 people (5%). Respondents in the very short category are 1 person (0.63%), short are 8 people (5.0%), normal are 142 people (89.8%), high are 7 people (4.4%) respondents. The study concludes that of the 158 students who were sampled, all of them were included in the good nutrition category, but there was 1 person (0.63% included in the very short category). ABSTRAK Anak sekolah merupakan salah satu kelompok rawan gizi yang perlu mendapatkan perhatian keadaan gizinya, agar di kemudian hari mereka menjadi sumber daya manusia yang berkualitas. Penelitian ini bertujuan untuk mengetahui gambaran status gizi siswa di SDN 61 Kota Timur Kota Gorontalo. Metode penelitian yang digunakan yaitu penelitian deskriptif. Populasi yaitu siswa/siswi kelas II, III, IV dan V SDN 61 Kota Timur Kota Gorontalo berjumlah 260 orang. Sampel penelitian ini berjumlah 158 orang. Variable dalam penelitian ini adalah variabel mandiri yaitu gambaran status gizi. Hasil Penelitian menunjukan dari 158 responden yang termasuk kategori gizi kurang berjumlah 2 orang (1,2%) , gizi baik (normal) berjumlah 88 orang (55,8%), beresiko gizi lebih berjumlah 38 orang (24%), gizi lebih berjumlah 22 orang (13,9%) dan obesitas berjumlah 8 orang (5%). Responden dengan kategori sangat pendek 1 orang (0,63%) , pendek berjumlah 8 orang (5,0%),normal berjumlah 142 orang (89,8%) , tinggi berjumlah 7 orang (4,4%) responden. Kesimpulan penelitian adalah dari 158siswa yang dijadikan sampel seluruhnya termasuk dalam kategori gizi baik,namunterdapat 1 orang (0,63% termasuk kategori sangat pendek.